Business strategy to develop the auto classified portals: case of otomart - Rifaie de Jong, Achmad; Dung Do, Anh (The Indonesian Journal of Business Administration, 2019)
Abstract - Indonesia automotive market has always been on the top of the markets among ASEAN countries. The interesting thing about the market is not merely about the production but also the car buying and selling process. Nowadays digital technologies started playing important roles in people day to day lives as we expect more accessible way of information anywhere, at any time and on any device. These include researching and buying car. Invention of auto classified portal plays an important role in these phenomenons.  OTOmart as online auto classified portals sees the opportunity to cater this massive market throughout digital mean which for decades classified ads were the domain of newspapers. As a new player in the industry OTOmart faces a challenge to find a way to gain a competitive advantage and successful monetization. It is imperative to move fast as the competition is getting tougher. This research focus in business strategy development in OTOmart as auto classified portal. The research methodology used in this final project is qualitative method. The information and data collection was gathered utilizing internal interview of OTOmart team and a survey to dealer and website visitor. Business solutions proposal offers an approach using linkages and interrelationship optimization as the research find there are some missing link on value creation in OTOmart. Moreover the strategy diamonds and business model generation complement the business solution for OTOmart to gain the competitive advantage, value proposition and monetization. The finding on business solution was formulated after the analysis on external and internal company situation. External factors are using PESTEL, Porter’s Five Forces, and Competitor Analysis. Meanwhile the internal analysis is using value chain analysis. To complement the analysis of internal and external the research also develops the SWOT analysis of OTOmart. Keywords: Competitive Advantage, Auto Classified Portal, Business Strategy, Business Model, Strategy Diamond, Linkages and Interrelationship